(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the added value of paraffin therapy combined with electroacupuncture and acupressure massage for pain relief and cervical range-of-motion improvement in patients with cervicobrachial syndrome due to cervical spondylosis. Subjects and Methods: This prospective, parallel-controlled, non-randomised intervention study included 60 patients treated at Thai Binh Provincial Traditional Medicine Hospital from April to November 2024. The study group received electroacupuncture, acupressure massage, and paraffin therapy; the control group received electroacupuncture and acupressure massage. Outcomes at D0, D7, and D15 were the VAS pain score, cervical range of motion, and radicular syndrome. Results: VAS scores decreased significantly in both groups after 7 and 15 days (p < 0.05). At D15, the study group had a lower VAS score than the control group (1.90 ± 0.80 vs. 2.70 ± 0.95; p < 0.05). Cervical range of motion improved in both groups, with greater gains in flexion, extension, and painful-side lateral bending in the study group at D15 (p < 0.05). The proportions of patients without radicular syndrome were 73.3% and 63.3%, respectively. Conclusion: Adding paraffin therapy to electroacupuncture and acupressure massage may provide additional short-term benefits for pain relief and partial improvement in cervical range of motion in patients with cervicobrachial syndrome due to cervical spondylosis.